The Struggle of African Americans against Racial Stereotypes Portrayed in Angie Thomas’s the Hate U Give (2017) - Hakim, Reyhan Azra; Al-Hafizh, Muhd. (Universitas Negeri Padang, 2024)
This thesis focuses on The Hate U Give, a novel written by African American author Angie Thomas. The purpose of this study is to find out the types of racial stereotypes imposed on African Americans and how they struggle against them. This study uses racial stereotypes theory in order to analyze the novel. The data are taken from the words, sentences, phrases, and quotations from the novel. The method used in this study is the descriptive analysis with a qualitative approach to attain a profound comprehension and delve into social intricacies. In conducting the analysis, a racial stereotypes approach was applied. The result shows that there are three different types of racial stereotypes found in the novel such as criminal stereotype, fatherless black stereotype, and black ghetto stereotype. The study also shows that characters in the novel struggle against racial stereotypes in their own way, and some even want to change people's perceptions of racial stereotypes towards African Americans.